Peranan Perempuan dalam Pembinaan Mental Spiritual Generasi Bangsa dalam Perspeksif Pendidikan Islam - Nur Wahib; Moh. Solehuddin (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2020)
In history before the arrival of Islam, women or women did not have proper dignity and worth, women were likened to merchandise that was worthy of being traded and even made into inheritance. The arrival of Islam by the Prophet Muhammad SAW has brought fresh air to women. Islam places women in an honorable position with the revelation of the Prophet Muhammad and gives them the freedom to go into various fields of choosing jobs that are in accordance with their nature to build society. In Islam, women are likened to the pillars of the state, if they are good, the state will be good, and if they are damaged, the state will be damaged. Furthermore, women have a set of rights and obligations that are closely related to the roles they carry, both roles in the family, community and nation and state in realizing the best future generation of the nation.